The 2008–2009 timber sector crisis in Africa and some lessons for the forest taxation regime - Karsenty, A.; Bayol, N.; Cerutti, P.O.; Ezzine-de-Blas, D.; Forni, E. (2010)
The 2008–2009 economic crisis has hit severely the African timber sector, with a brutal collapse of the foreign demand. Overall, the impact has been of around the loss of one-third of export and production. Companies have been unable to pay the fixed costs represented by the area tax, and this last has been suspended in several countries, notably in Cameroon. The brutality of the crisis has highlighted the absence of automatic correctors embodied in the fiscal system itself. A first, even though insufficient, answer could be to index the area fee to a nation-representative bundle of timber species FOB values. The absence of organisations such as the World Bank in the dialogue between the governments and the private sector is striking, given their past involvement in the forests fiscal reforms in central Africa. The current focus given on REDD, seen by many as an instrument for entering in a post-logging time could explain this passivity. Large FSC-certified companies announced their intention to sell out their concessions in Congo and Gabon. This could prefigure a new picture with various types of small logging enterprises filling the vacuum left by formal industry and some FSC-certified concessionaires replaced by large but less environmentally responsible companies